Comparison of Treacher Collins Syndrome and Pierre Robin Sequence: a CBCT study - Kato, Renata Mayumi (2020)
Introduction: Treacher Collins Syndrome (TCS) and non-syndromic Pierre Robin Sequence (PRS) share mandibular deficiency as a similar clinical finding. The ramus-body ratio, the degree of mandibular asymmetry and the condyle morphology were not compared between TCS and PRS. Objectives: The aim of this study was to compare the facial morphology and mandibular dimensions in individuals with TCS and PRS. Methods: The sample consisted of cone-beam computed tomography (CBCT) from a single center. Group TCS was composed by 17 individuals with TCS and presented an average age of 11.5 years (7 males, 10 females). Group PRS was paired by sex and age with the Group TCS. Quantitative evaluations were performed using CBCT-derived cephalometric reconstructions (2D) and three-dimensional reconstructions of the mandible. The softwares used was Dolphin (Dolphin Imaging 11.0 & Management Solutions, California, United States) and Mimics Innovation Suite 17.0 (Materialize, Leuven, Belgium). Intergroup comparison was performed using the independent t test/Mann-Whitney and the ANOVA/Tukey test for twodimensional and three-dimensional analysis, respectively (p <0.05). Results: The cranial base and the sagittal position of the maxilla were similar in both groups. The mandible in group TCS showed a higher degree of asymmetry than group PRS. The transversal dimensions of the mandibular ramus and condyle, the effective mandibular and mandibular body length and the condyle height were reduced in TCS compared PRS. Group TCS exhibited a greater gonial angle with a more severe vertical growth pattern when compared to PRS. Conclusion: The most important dentoskeletal differences between the craniofacial anomalies were observed in the mandible. Treacher Collins Syndrome had a smaller, more asymmetrical and more vertical mandible than the non-syndromic Pierre Robin Sequence